Role of marsupial tammar wallaby milk in lung maturation of pouch young - Modepalli, Vengamanaidu (BMC Dev Biol, 2015)
BACKGROUND: Marsupials such as the tammar wallaby (M.Eugenii) have a short gestation (29.3 days) and at birth the altricial young resembles a fetus, and the major development occurs postnatally while the young remains in the mother’s pouch. The essential functional factors for the maturation of the neonate are provided by the milk which changes in composition progressively throughout lactation (300 days). Morphologically the lungs of tammar pouch young are immature at birth and the majority of their development occurs during the first 100 days of lactation. RESULTS: In this study mouse embryonic lungs (E-12) were cultured in media with tammar skim milk collected at key time points of lactation to identify factors involved in regulating postnatal lung maturation. Remarkably the embryonic lungs showed increased branching morphogenesis and this effect was restricted to milk collected at specific time points between approximately day 40 to 100 lactation. Further analysis to assess lung development showed a significant increase in the expression of marker genes Sp-C, Sp-B, Wnt-7b, BMP4 and Id2 in lung cultures incubated with milk collected at day 60. Similarly, day 60 milk specifically stimulated proliferation and elongation of lung mesenchymal cells that invaded matrigel. In addition, this milk stimulated proliferation of lung epithelium cells on matrigel, and the cells formed 3-dimensional acini with an extended lumen. CONCLUSIONS: This study has clearly demonstrated that tammar wallaby milk collected at specific times in early lactation contains bioactives that may have a significant role in lung maturation of pouch young. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12861-015-0063-z) contains supplementary material, which is available to authorized users.